1989
DOI: 10.1007/bf01974573
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic peptide has no direct cardiac actions

Abstract: The electrophysiologic, inotropic, and muscarinic effects of antiarrhythmic peptide (AAP) were examined in canine cardiac Purkinje fibers, ferret papillary muscle, and canine cardiac membranes, respectively. Aside from a prolongation of time to peak force in papillary muscle, no biologically significant effects of AAP could be determined in any preparation, suggesting that its antiarrhythmic effects are not mediated by direct membrane actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…These observations are in accordance with previous findings for these compounds and for the endogenous antiarrhythmic peptide AAP and the synthetic derivative HP-5 (Argentieri et al, 1989;Dhein et al, 1994;Kjølbye et al, 2002;Xing et al, 2003). In isolated rabbit hearts subjected to hypokalemic ischemia-reperfusion, 0.1 nM HP-5 significantly reduced dispersion of APD 90 without affecting average APD, heart rate, contractility, or coronary flow (Kjølbye et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are in accordance with previous findings for these compounds and for the endogenous antiarrhythmic peptide AAP and the synthetic derivative HP-5 (Argentieri et al, 1989;Dhein et al, 1994;Kjølbye et al, 2002;Xing et al, 2003). In isolated rabbit hearts subjected to hypokalemic ischemia-reperfusion, 0.1 nM HP-5 significantly reduced dispersion of APD 90 without affecting average APD, heart rate, contractility, or coronary flow (Kjølbye et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…In isolated rabbit hearts subjected to hypokalemic ischemia-reperfusion, 0.1 nM HP-5 significantly reduced dispersion of APD 90 without affecting average APD, heart rate, contractility, or coronary flow (Kjølbye et al, 2002). In isolated canine Purkinje fibers, it was shown that AAP did not affect inotropy or any of the electrophysiological parameters measured (maximum diastolic potential, action potential amplitude, maximum rate of depolarization, and action potential duration at 50 and 95% repolarization) (Argentieri et al, 1989). In the isolated rabbit heart, AAP10 had no effect on mean action potential duration, left ventricular end-diastolic pressure, coronary flow, QRS duration, or on the PQ interval (Dhein et al, 1994).…”
Section: Discussionmentioning
confidence: 92%
“…In isolated rabbit hearts subjected to regional ischemia, HP‐5 specifically reduced dispersion of monophasic action potential onset and duration without affecting action potential duration, heart rate, maximum developed left ventricular pressure, or mean coronary flow 17 . It was shown in isolated canine Purkinje fibers that naturally occurring AAP did not affect inotropy or any of the electrophysiologic parameters measured 26 . Similarly, no effects were seen in the isolated rabbit or guinea pig hearts with AAP10 in concentrations up to 1 μM 18 .…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the mechanism of action of AAPnat, electrophysiological experiments on canine Purkinje fibers showed that the transmembrane action potential was not altered (Argentieri et al, 1989), thus indicating that transmembrane ionic currents are not involved. Dhein and coworkers (Dhein et al, 1994;Müller et al, 1997a, b;Dhein et al, 2001a) demonstrated that the effect of AAPnat and related peptides consists of an improvement of cellular coupling and an increase in gap junctional conductance.…”
Section: Modulation By Antiarrhythmic Peptidesmentioning
confidence: 97%